EFL TEACHERS’ REFLECTION IN THE IMPLEMENTATION OF ONLINE FLIPPED CLASSROOM: CHALLENGES AND STRATEGIES - Farida Noor Rohmah; David Sulistiawan Aditya (English Review: Journal of English Education, 2023)
The implementation of online flipped classroom was one of the impacts occurred due to Covid-19 pandemic in educational sector. This sudden shift caused challenges for EFL teachers. However, only a few studies researched the teachers’ challenges in implementing fully-online flipped classroom and the ways they solved them. Therefore, this study aims to explore the teachers’ challenges in implementing fully-online flipped classroom and their strategies to deal with them. This study employed a narrative inquiry method and the data were gathered with a semi-structured interview from three EFL teachers from a private university in Yogyakarta. The results showed that the teachers faced challenges including students’ motivation and engagement, students’ mixed ability, assessment, resistance to change and teachers’ workload. Teachers’ strategies were: maximizing synchronous meeting, providing meaningful and personalized feedback, assigning groupwork, utilizing formative assessment and collaborating with colleagues. This study can help the teachers to identify their challenges in implementing flipped classroom in an online environment and find the solutions.